Variations in concerns reported on the patient concerns inventory in patients with head and neck cancer from different health settings across the world. Issue 3 (13th December 2019) - Rogers, Simon N.; Alvear, Alvaro; Anesi, Alexandre; Babin, Emmanuel; Balik, Ali; Batstone, Martin; Brockmeyer, Phillipp; Carrasco, Claudia Celedon; Chien, Chih‐Yen; Chirila, Magdalena; Dholam, Kanchan P.; Doss, Jennifer G.; et al.
Abstract: Background: The aim was to collate and contrast patient concerns from a range of different head and neck cancer follow‐up clinics around the world. Also, we sought to explore the relationship, if any, between responses to the patient concerns inventory (PCI) and overall quality of life (QOL). Methods: Nineteen units participated with intention of including 100 patients per site as close to a consecutive series as possible in order to minimize selection bias. Results: There were 2136 patients with a median total number of PCI items selected of 5 (2‐10). "Fear of the cancer returning" (39%) and "dry mouth" (37%) were most common. Twenty‐five percent (524) reported less than good QOL. Conclusion: There was considerable variation between units in the number of items selected and in overall QOL, even after allowing for case‐mix variables. There was a strong progressive association between the number of PCI items and QOL.